2016
DOI: 10.1136/neurintsurg-2016-012403
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of intracranial aneurysms with the LVIS device: a systematic review

Abstract: Our systematic review suggests that endovascular treatment of intracranial aneurysms with the LVIS device is feasible, safe, and effective in the short term. However, the rate of thromboembolic complications is not negligible. Further prospective studies are needed to evaluate the long-term efficacy and safety of the LVIS device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 23 publications
6
70
0
1
Order By: Relevance
“…The complete occlusion rate at follow-up angiography was 84.3%. However, a not negligible thromboembolic event rate of 4.9% was reported, as well as an in-stent thrombosis rate of 1.4% 33. Regarding long-term complications for Y-stenting constructs, we found a non-negligible risk of potentially permanent narrowing of the second stent when performing a ‘coil through technique’ owing to small pore size of the initial closed-closed stent construct 26…”
Section: Discussionmentioning
confidence: 77%
“…The complete occlusion rate at follow-up angiography was 84.3%. However, a not negligible thromboembolic event rate of 4.9% was reported, as well as an in-stent thrombosis rate of 1.4% 33. Regarding long-term complications for Y-stenting constructs, we found a non-negligible risk of potentially permanent narrowing of the second stent when performing a ‘coil through technique’ owing to small pore size of the initial closed-closed stent construct 26…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, for the Leo baby stent, the reported morbidity and mortality rates were 3.8% and 0%, respectively 13. The incidence of morbidity and mortality were 2.8% and 2% for the Enterprise stent14 and 1.4% and 0% for the LVIS stent, respectively 19…”
Section: Discussionmentioning
confidence: 94%
“…In a smaller number of patients when LVIS Jr ‘C’ was used, the technical success was also 100% in the previous series,13 possibly owing to the improved radial force in LVIS Jr ‘C’ stents. A systematic review of all LVIS stents showed technical success of 96.8% 14. The technical success rates have been reported to be 94% with Neuroform,7 95% with Enterprise stents,5 and 100% with Solitaire stents 9…”
Section: Discussionmentioning
confidence: 99%
“…A systemic review of the use of LVIS stents reported a thromboembolic rate of 4.9% and hemorrhagic complication rate of 2.1% 14. Mocco et al 5 reported 2.8% permanent morbidity and 2% mortality associated with use of Enterprise stents.…”
Section: Discussionmentioning
confidence: 99%